Guided Discovery Learning with Web Simulations in Digital Literacy and Critical Thinking: Pembelajaran Guided Discovery Berbantuan Simulasi Web pada Literasi Digital dan Berpikir Kritis - Elisabeth Asima Rohana Sinaga; Ani Rusilowati (Academia Open, 2026)
General Background: The integration of digital technology in education requires learning approaches that support digital literacy and critical thinking development in science education. Physics learning in junior high schools often remains teacher-centered, resulting in limited student participation and shallow conceptual understanding. Specific Background: Web-based simulations provide interactive environments that enable students to explore scientific concepts and digital resources, while the Guided Discovery Learning model encourages active investigation and conceptual discovery during instruction. Knowledge Gap: Despite the potential of these approaches, physics learning frequently focuses on content delivery and problem solving without optimally integrating digital exploration and guided discovery processes. Aims: This study aims to analyze the implementation of Guided Discovery Learning assisted by Web-Based Simulation in improving digital literacy and critical thinking skills among Grade IX junior high school students studying magnetism and its applications. Results: A quasi-experimental pretest–posttest control group design involving two classes demonstrated significant differences between experimental and control groups (Sig. < 0.001). The experimental class showed higher improvements with N-gain values of 0.66 for digital literacy (moderate category) and 0.71 for critical thinking (high category). Novelty: The study presents empirical evidence on the integration of guided discovery learning with web-based simulation to support technology-mediated physics learning and student engagement. Implications: The findings indicate that contextual learning designs combining discovery-based instruction and digital simulations can support the development of digital literacy and critical thinking in junior high school physics learning, although implementation also depends on student readiness, digital competence, and environmental support. Highlights • Guided discovery learning with web simulations produced higher learning gains in experimental classes.• Digital literacy improvement reached moderate category with N-gain score of 0.66.• Critical thinking achievement reached high category with N-gain value of 0.71. Keywords Guided Discovery Learning; Web-Based Simulation; Digital Literacy; Critical Thinking; Physics Education